Before Förster. Initial excitation in photosynthetic light harvesting. Issue 34 (12th July 2019) - Karki, Khadga J.; Chen, Junsheng; Sakurai, Atsunori; Shi, Qi; Gardiner, Alastair T.; Kühn, Oliver; Cogdell, Richard J.; Pullerits, Tönu
Abstract : Fluorescence detected double quantum coherence 2D spectroscopy reveals strong correlation between weakly coupled pigment pools directly after absorption of light before the Förster transfer regime sets in. Abstract : Electronic 2D spectroscopy allows nontrivial quantum effects to be explored in unprecedented detail. Here, we apply recently developed fluorescence detected coherent 2D spectroscopy to study the light harvesting antenna 2 (LH2) of photosynthetic purple bacteria. We report double quantum coherence 2D spectra which show clear cross peaks indicating correlated excitations. Similar results are found for rephasing and nonrephasing signals. Analysis of signal generating quantum pathways leads to the conclusion that, contrary to the currently prevailing physical picture, the two weakly coupled pigment rings of LH2 share the initial electronic excitation leading to quantum mechanical correlation between the two clearly separate absorption bands. These results are general and have consequences for the interpretation of initially created excited states not only in photosynthesis but in all light absorbing systems composed of weakly interacting pigments where the excitation transfer is commonly described by using Förster theory. Being able to spectrally resolve the nonequilibrium dynamics immediately following photoabsorption may provide a glimpse to the systems' transition into the Förster regime.